2018
DOI: 10.1103/physrevb.97.075140
|View full text |Cite
|
Sign up to set email alerts
|

Importance of nonlocal electron correlation in the BaNiS2 semimetal from quantum oscillations studies

Abstract: By means of Shubnikov-de-Haas and de-Haas-van-Alphen oscillations, and ab initio calculations, we have studied the Fermi surface of high-quality BaNiS 2 single crystals, with mean free path l ∼ 400Å. The angle and temperature dependence of quantum oscillations indicates a quasi-twodimensional Fermi surface, made of an electron-like tube centred at Γ, and of 4 hole-like cones, generated by Dirac bands, weakly dispersive in the out-of-plane direction. Ab initio electronic structure calculations, in the density f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Due to the vanishing density of states at the Dirac or Weyl points, the screening of the Coulomb interaction is altered, and long-range Coulomb interaction is a crucial ingredient in the description of these materials [30]. Hence, the nodal-line semimetals exhibit strong nonlocal correlations [31,32], which are not captured by a local Hubbard U as used in DFT + U . This represents therefore an interesting potential application of our extended ACBN0 functional.…”
Section: A Zrsisementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the vanishing density of states at the Dirac or Weyl points, the screening of the Coulomb interaction is altered, and long-range Coulomb interaction is a crucial ingredient in the description of these materials [30]. Hence, the nodal-line semimetals exhibit strong nonlocal correlations [31,32], which are not captured by a local Hubbard U as used in DFT + U . This represents therefore an interesting potential application of our extended ACBN0 functional.…”
Section: A Zrsisementioning
confidence: 99%
“…In Refs. [31,33], it was shown that hybrid functional calculations with a fraction of exact exchange of 7% reproduce best the experimental results, compared to the standard fraction of 25% used in the HSE06 functional [34]. We employed the experimental lattice constant of 3.623 Å and we sampled the real space using a spacing of 0.3 bohrs and the Brillouin zone using a 7 × 7 × 3 kpoint grid.…”
Section: A Zrsisementioning
confidence: 99%
“…The metallic end member, BaNiS 2 , is a Pauli paramagnet with the tetragonal (P 4/nmm) structure, exhibiting Ba layers alternating with layers of NiS 5 square pyramids [3]. BaNiS 2 has recently been reported to be a compensated semimetal with topological band crossings [4]. In the P 4/nmm space group, the NiS 5 square-pyramids are distorted such that the apical Ni-S bond lengths are slightly longer than the basal Ni-S lengths.…”
Section: Introductionmentioning
confidence: 99%
“…The Hubbard U was evaluated for the d orbitals of Zr, and limited to the nearest-neighbor interaction for the intersite V. We employed fully relativistic pseudopotentials with a 15 × 15 k-point grid and a grid spacing of 0.158 Å −1 to sample the two-dimensional Brillouin zone. More details about geometry optimization and a comparison with DFT þ U and hybrid functionals can be found in the Supplemental Material [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
mentioning
confidence: 99%